The slower the better: how sperm capacitation and acrosome reaction is modified in the presence of estrogens - Sebkova, Natasa; Cerna, Martina; Ded, Lukas; Peknicova, Jana; Dvorakova-Hortova, Katerina (Reproduction, 2012)
In order for mammalian sperm to obtain a fertilizing ability, they must undergo a complex of molecular changes, called capacitation. During capacitation, steroidal compounds can exert a fast nongenomic response in sperm through their interaction with plasma membrane receptors, and activate crucial signaling pathways leading to time-dependent protein tyrosine phosphorylation (TyrP). Estrogen receptor beta was detected in epididymal mouse sperm; therefore, the effect of 17B-estradiol, estrone, estriol, and 17A-ethynylestradiol on mouse sperm capacitation in vitro was investigated. The effect was evaluated by positive TyrP in sperm heads and in the whole sperm lysates. Simultaneously, the state of the acrosome after the calcium ionophore-induced acrosome reaction was assessed. Generally, estrogens displayed a time and concentration-dependent stimulatory effect on sperm TyrP during capacitation. In contrast, the number of sperm that underwent the acrosome reaction was lower in the experimental groups. It has been demonstrated that both natural and synthetic estrogens can modify the physiological progress of mouse sperm capacitation. The potential risk in the procapacitation effect of estrogens can also be seen in the decreased ability of sperm to undergo the acrosome reaction. In conclusion, the capacitating ability of sperm can be significantly lowered by increasing the level of estrogens in the environment.
Keywords: Animals; vztah mezi dávkou a účinkem léčiva; akrozomální reakce; kapacitace spermií; Acrosome Reaction; Time Factors; časové faktory; Mice; Osmolar Concentration; Mice, Inbred BALB C; myši; estrogeny; Dose-Response Relationship, Drug; osmolární koncentrace; Estrogens; Male; fosforylace; Semen Analysis; myši inbrední BALB C; analýza spermatu; Sperm Capacitation; zvířata; mužské pohlaví; Protein-Tyrosine Kinases; Phosphorylation; tyrosinkinasy